2020
DOI: 10.21873/invivo.12128
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Patients at High Risk for Postsurgical Hypoparathyroidism

Abstract: Background/Aim: Postsurgical hypoparathyroidism (PostHypo) is a common complication after total thyroidectomy. We studied the risk factors associated with PostHypo. Patients and Methods: The study included 109 women, (mean age: 50.7±10.75 years), who underwent total thyroidectomy for thyroid diseases. Results: Based on the development of biochemical hypocalcemia on the first postoperative day following total thyroidectomy, (cCa<8.4 mg/dl), 37 women developed PostHypo and 72 did not. Younger age, a lower preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Main postoperative complications of thyroidectomy are injuries to the parathyroid glands and to the laryngeal nerves, but also tracheal compression secondary to hematoma or tracheomalacia. 5,6,9,10 Another possible differential diagnosis of dyspnea is a pulmonary edema due to volume overload, which can be caused by a membranous nephropathy linked to hypothyroidsm. 11 An injury of the parathyroid glands can lead to the manifestation of temporary and even permanent hypocalcemia due to low parathyroid hormone levels.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Main postoperative complications of thyroidectomy are injuries to the parathyroid glands and to the laryngeal nerves, but also tracheal compression secondary to hematoma or tracheomalacia. 5,6,9,10 Another possible differential diagnosis of dyspnea is a pulmonary edema due to volume overload, which can be caused by a membranous nephropathy linked to hypothyroidsm. 11 An injury of the parathyroid glands can lead to the manifestation of temporary and even permanent hypocalcemia due to low parathyroid hormone levels.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…11 An injury of the parathyroid glands can lead to the manifestation of temporary and even permanent hypocalcemia due to low parathyroid hormone levels. 10 It occurs in up to 15% of postoperative patients, who can be symptomatic or asymptomatic. 5,10,12 Especially at risk are patients who already present low levels of parathyroid hormone at surgery and in who the parathyroid glands are resected.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a meta-analysis of 115 observational studies of bilateral thyroid surgery, age was not significantly associated with postoperative transient hypocalcemia, while female gender and Graves' disease were independent risk factors [ 20 ]. Several studies have suggested that autoimmune thyroiditis and higher cancer stages could be related to a higher risk of postoperative hypoparathyroidism, but there are conflicting reports [ 4 , 9 , 11 , 20 ]. In our study, gender, age, Hashimoto's thyroiditis, tumor size, and N stage were not significantly associated with postoperative hypoparathyroidism.…”
Section: Discussionmentioning
confidence: 99%